PENGARUH KONSUMSI KULIT MANGGIS TERHADAP PENURUNAN KADAR GULA DARAH PADA PENDERITA DIABETES MELLITUS DI DESA METESEH BOJA KENDAL TAHUN 2013 - Budi Herminto; Diyono -; Shinta Dewi Kusuma (KOSALA : Jurnal Ilmu Kesehatan, 2014)
Abstract Background. Prevalensidiabetes mellitus in Indonesia potentially increased dramatically from 8.4 million people in 2000 to 21.3 million people in 2030. Diabetes mellitus may develop so bad with various complicated, diabetus mellitus of year to year growing a wide range of treatment options including non- medicinal chemistry ( Hebal ) . One type of therapy is continuously studied using mangosteen peel efectivitness. Research Objectives. Knowing the effect of the consumption of mangosteen rind to decrease blood sugar in the Village District of Boja Meteseh Kendal This is a research Methods. Quasi experiment with pre- post design eksperimental.Responden study are all patients with diabetes mellitus in the village of Boja Meteseh many as 17 people , as many as 16 samples taken. Sampling technic used was simple random sampling . Data obtained by the method of observation of assessing the results of measurements of blood sugar levels before and after taking of mangosteen skin . The data were processed with pairet t - test ( p = 0.05 ) using SPSS 18 . Results : ( 1 ) blood sugar levels before taking mangosteen peel at the most in the range of 301-400 mg / dL with a percentage of 43.75 % , the lowest blood sugar levels in the category of 501-600 mg / dL , with a percentage of 12.5 % , with an average value of 392.63 . ( 2 ) Blood sugar levels after consumption of mangosteen peel at the most in the range of 200-300 mg / dL , the percentage of blood sugar levels are the lowest in the category of 501-600 mg / dL , with a percentage of 12.5 % , with an average value of 371.31 mg / dL ( 3 ) There are significant differences in blood sugar levels before and after consuming mangosteen peel with a value of 0.001 t - Test Conclusion : Consumption of mangosteen peel significant effect on lowering blood sugar levels by t - test results of 5 % ( 0.05), obtained P value of 0.001. Keywords: Blood Sugar Levels, Skin Mangosteen, Diabetes Mellitus